2010
DOI: 10.1002/hep.23796
|View full text |Cite
|
Sign up to set email alerts
|

Associations between serum lipids and hepatitis C antiviral treatment efficacy

Abstract: Approximately one half of patients who undergo antiviral therapy for chronic hepatitis C virus (HCV) genotype 1 infection do not respond to treatment. African Americans (AAs) are less responsive to treatment than Caucasian Americans (CAs), but the reasons for this disparity are largely unknown. Recent studies suggest that serum lipids may be associated with treatment response. The aims of this study were to evaluate baseline and changes in serum lipids during therapy, determine whether serum lipids are associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
64
2
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 43 publications
6
64
2
2
Order By: Relevance
“…Of particular note, we found higher pretreatment serum miR-122 levels among patients with CHC who showed cEVR and SVR after pegIFN/RBV therapy, especially patients with IL-28B TT genotype or HCV genotype 2. As shown in previous studies (27)(28)(29), we found lower pretreatment BMI, GGT, and triglyceride levels and Metavir score, as well as higher serum miR-122 level, to predict SVR in univariate analysis. Because of the dominant predictability of IL-28B TT genotype and small sample size, the risk estimate of serum miR-122 was statistically insignificant to predict SVR (OR, 4.12; 95% CI, 0.64-26.58).…”
Section: Discussionsupporting
confidence: 83%
“…Of particular note, we found higher pretreatment serum miR-122 levels among patients with CHC who showed cEVR and SVR after pegIFN/RBV therapy, especially patients with IL-28B TT genotype or HCV genotype 2. As shown in previous studies (27)(28)(29), we found lower pretreatment BMI, GGT, and triglyceride levels and Metavir score, as well as higher serum miR-122 level, to predict SVR in univariate analysis. Because of the dominant predictability of IL-28B TT genotype and small sample size, the risk estimate of serum miR-122 was statistically insignificant to predict SVR (OR, 4.12; 95% CI, 0.64-26.58).…”
Section: Discussionsupporting
confidence: 83%
“…However, serum lipoprotein disturbances in other genotypes are an issue that has been under discussion. In addition, disturbances in lipoprotein profiles have been reported in patients who were not responsive to IFN-based antiviral therapy in comparison to responsive patients with chronic HCV-G1 infection [26,27]. However, whether or not dyslipoproteinemia is an independent factor affecting the efficacy of IFN-based therapy remains controversial.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, distortion of serum lipid levels has been widely observed in connection with virological outcome of IFN-based antiviral therapy, especially in HCV-G1 infection. Lower LDL-C, HDL-C, TC and/or TG was reported to be a possible predictor for unfavorable response to IFN-based therapy [24,26,27]. However, after the discovery of a genetic polymorphism near the human IL28B gene as the most potent predictor of the outcome of IFN-based therapy, the distortion of serum lipid levels is no longer thought to be an independent factor, but rather a confounding variable for predicting therapeutic efficacy [28].…”
Section: Introductionmentioning
confidence: 99%
“…In the bivariate analysis, IR was associated with age and anthropometric factors (BMI, waist circumference and weight categories); however, this association was not found in the multivariate analysis. Some studies also showed the association of age, waist circumference, and BMI to IR among HCV patients (9,10,11,13,18). IR was also associated with higher mean values of triglycerides and is most likely the result of the characteristics of the HCV replication cycle.…”
Section: Discussionmentioning
confidence: 98%